An An Experimental Investigation of Tensile Strength and Impact Energy of Polymeric Foams-OPEFB Fiber Sandwich Panels Composite - Arief, Dodi Sofyan; Sitio, Erik Johanes; Rahmat, Ridho Zarli; Badri, Muftil (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
This paper discusses about an experimental investigation of tensile strength and impact properties of polymeric foams-OPEFB fiber sandwich panels composite with various directions of palm empty fruit bunches fiber, vacuum pressure, and foam thickness. In this study, the manufacture of specimens with different fiber directions will then be tested and analyzed for each direction of fiber. The results of the analysis of composite specimens in the study were evaluated and compared with each other. The purpose of this study was to obtain impact energy and tensile strength of composite plates. In the manufacture of sandwich panel specimens carried out by varying the pump pressure, foam thickness, and the direction of the preparation of the fiber and carried out by the vacuum method. From the test results, it was found that the highest tensile strength was composite specimens with vertical fiber direction is specimens with three vertical panels of fiber direction, vacuum pressure 6 cm Hg, and foam thickness is 1.5 mm with tensile strength is 22.5 N/mm2, while the highest impact energy is the specimen with vertical fiber direction is the specimen with the fiber direction of the three vertical panels, the vacuum pressure is 6 cm Hg, and foam thickness of 1.5 mm with an impact price of 0.16 J/mm2. From this study it can be concluded that the fiber direction is 53% higher than the direction of the combined fibers vertically, horizontally, and vertically in absorbing impact loads, also 83% higher than the vertical, 45°, and horizontal combined fibers in absorbing impact loads It also has a tensile strength of 10% higher than the vertical, horizontal and vertical combined fiber direction, also has a tensile strength of 15% higher than the vertical, 45° and horizontal combined fiber direction.